To divide the expression \( 56r - 12 \) by \( 4t \), you can separate each term in the numerator:
\[ \frac{56r - 12}{4t} = \frac{56r}{4t} - \frac{12}{4t} \]
Now, simplify each part:
-
Simplifying \( \frac{56r}{4t} \): \[ \frac{56r}{4t} = \frac{56}{4} \cdot \frac{r}{t} = 14 \cdot \frac{r}{t} = \frac{14r}{t} \]
-
Simplifying \( \frac{12}{4t} \): \[ \frac{12}{4t} = \frac{12}{4} \cdot \frac{1}{t} = 3 \cdot \frac{1}{t} = \frac{3}{t} \]
Putting it all together, we get:
\[ \frac{56r - 12}{4t} = \frac{14r}{t} - \frac{3}{t} \]
Thus, the final answer is:
\[ \frac{14r - 3}{t} \]